2016
DOI: 10.1016/j.ihj.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Complications encountered in coronary chronic total occlusion intervention: Prevention and bailout

Abstract: Despite the continuing developments of improved medical devices and increasing operator expertize, coronary chronic total occlusion (CTO) remains as one of the most challenging lesion subsets in interventional cardiology. Percutaneous coronary intervention (PCI) of CTO is a complex procedure carrying the risk of complications that are responsible for significant morbidity and mortality. The complications can be classified as coronary (such as coronary occlusion, perforation, device embolization, or entrapment)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…In one case report, septal hematoma manifesting as an echo-free space caused asymptomatic bigeminy and severe chest pain and was resolved spontaneously 42 . Perforation into cardiac chamber usually does not result in complications until and unless there is balloon dilatation or advancement of additional device 43, 44. Perforation causing hemorrhage within the myocardium rather than the ventricle leads to gradual enlargement of hematoma which needs to be treated by hemostasis.…”
Section: Complications Encountered During Retrograde Proceduresmentioning
confidence: 99%
“…In one case report, septal hematoma manifesting as an echo-free space caused asymptomatic bigeminy and severe chest pain and was resolved spontaneously 42 . Perforation into cardiac chamber usually does not result in complications until and unless there is balloon dilatation or advancement of additional device 43, 44. Perforation causing hemorrhage within the myocardium rather than the ventricle leads to gradual enlargement of hematoma which needs to be treated by hemostasis.…”
Section: Complications Encountered During Retrograde Proceduresmentioning
confidence: 99%
“…Even if this condition can easily be identified through coronary angiography, it is least preferred to be treated in interventional cardiology due to increased failure rates. [ 1 ] In addition, treatment for CTO varied from 1 healthcare center to another and from region to region. [ 2 , 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, women tend to have smaller body size and coronary arteries than men that are more susceptible to CICAD during PCI [ 28 , 33 ]. In terms of PCI of a complex coronary anatomy, previous studies demonstrated that a high rate of procedural complications in cases of complex PCI [ 8 , 9 ]. The studies conducted in the era of bare-metal stents and first-generation DES demonstrated that CTO (14.3% vs 5.2%, p < 0.001), calcification (30.0% vs 13.7%, p = 0.002), ACC/AHA lesion type B2 or C (44.2% vs 28.3%, p = 0.002) were observed at a higher rate in patients with final dissection [ 5 ], and severely calcified long and tortured lesions were associated with the increased risk of dissection [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, this advancement has led more interventionists to perform PCI in patients with more high-risk anatomic features, such as chronic total occlusion (CTO), bifurcation, and left main trunk lesions [ 7 ]. Consequently, procedural complications such as abrupt closure, perforation, device embolization, and CICAD have re-emerged and are under the spotlight in the contemporary PCI era [ 8 , 9 ]. Although there were several previously published series, their small size has limited the robustness of any conclusion; in particular, the impact of flow-limiting vs flow-recovered CICAD has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%